Sphingosine 1-Phosphate (S1P) Receptors 1 and 2 Coordinately Induce Mesenchymal Cell Migration through S1P Activation of Complementary Kinase Pathways - Quint, Patrick (American Society for Biochemistry and Molecular Biology, 2013)
Normal bone turnover requires tight coupling of bone resorption and bone formation to preserve bone quantity and structure. With aging and during several pathological conditions, this coupling breaks down, leading to either net bone loss or excess bone formation. To preserve or restore normal bone metabolism, it is crucial to determine the mechanisms by which osteoclasts and osteoblast precursors interact and contribute to coupling. We showed that osteoclasts produce the chemokine sphingosine 1-phosphate (S1P), which stimulates osteoblast migration. Thus, osteoclast-derived S1P may recruit osteoblasts to sites of bone resorption as an initial step in replacing lost bone. In this study we investigated the mechanisms by which S1P stimulates mesenchymal (skeletal) cell chemotaxis. S1P treatment of mesenchymal (skeletal) cells activated RhoA GTPase, but this small G protein did not contribute to migration. Rather, two S1P receptors, S1PR1 and S1PR2, coordinately promoted migration through activation of the JAK/STAT3 and FAK/PI3K/AKT signaling pathways, respectively. These data demonstrate that the chemokine S1P couples bone formation to bone resorption through activation of kinase signaling pathways.